Thermodynamic analysis of a semi-lean solution process for energy saving via rectisol wash technology. (1st July 2021) - Yang, Sheng; Zhang, Lu; Xie, Nan; Gu, Zhaohui; Liu, Zhiqiang
Abstract: Currently, it is of great significance to develop energy-saving technologies. Rectisol wash technology is becoming more and more popular in the industrial field due to its excellent performance. In order to reduce the energy consumption, a semi-lean solution process based on the Rectisol wash technology is proposed in this paper. The Cubic-Plus-Association (CPA) and Predictive Soave–Redlich–Kwong (PSRK) property methods are selected for the simulations in Aspen Plus. Two scenarios are proposed for the energy and exergy analysis. Results show that 50% SP3-reflux ratio is the optimal point in both scenarios from the energy view, and the optimal SP3-reflux ratios for scenario 1 and scenario 2 are 40% and 43% from the exergy view, respectively. In addition, the analysis results of related parameters in both scenarios show that increasing the SP1-spitting ratio or decreasing the SP2-spitting ratio has a positive effect on CO2 production; the H2 S concentration in CO2 product first increases and then decreases while either ratio increases. The stripping N2 flowrate has a significant impact on the H2 S concentration in Claus gas. This paper may guide for further study of the semi-lean solution process and provide a better understanding for Rectisol technology. Highlights: A concept of a semi-lean solution process for energy saving based on Rectisol wash process is proposed. Thermodynamic performances and key parameters are analyzed and compared. 50% SP3-reflux ratio is the optimal point in both scenarios from the energy view. The optimal SP3-reflux ratios for scenario 1 and scenario 2 are 40% and 43% from the exergy view.